Strategi Digital Menuju Kesuksesan Perusahaan Pialang: Optimasi Pemasaran Dan Kualitas Produktivitas Dalam Bersaing - Ni Matul Azizah; Sulastri Irbayuni (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This journal article discusses the influence of digital marketing strategies in advancing competitive brokerage firms. Optimized marketing and quality productivity are keys to the achieving company success or in other words, finding the efficiency point in the marketing strategy that is most suitable for brokerage companies. Through this journal article, there is a discussion that can be used to provide insight into brokerage companies that survive in today's digital era, as well as quality productivity by marketing and sales in brokerage companies with marketing optimization. This discussion was conducted in one of the brokerage companies, PT Victory International Futures Spazio branch with a communication model with permanent employees at the company's branch.